Acceptability and feasibility of weight management programmes for adults with severe obesity: a qualitative systematic review - Graeme Maclennan; David Cooper; Paul Aveyard; Magaly Aceves-Martins; Fiona Stewart; Jennifer Logue; Zoë C Skea; Michal Shimonovich; Clare Robertson; Alison Avenell; Elisabet Jacobsen; Dwayne Boyers; et al. (BMJ Open)
Objectives To improve our understanding of the acceptability of behavioural weight management programmes (WMPs) for adults with severe obesity.Design A systematic review of qualitative evidence.Data sources Medline, Embase, PsycINFO, CINAHL, SCI, SSCI and CAB abstracts were searched from 1964 to May 2017.Eligibility criteria Papers that contained qualitative data from adults with body mass index (BMI) ≥35 kg/m2 (and/or the views of providers involved in their care) and considered issues about weight management.Data extraction and synthesis Two reviewers read and systematically extracted data from the included papers which were compared, and contrasted according to emerging issues and themes. Papers were appraised for methodological rigour and theoretical relevance using Toye’s proposed criteria for quality in relation to meta-ethnography.Results 33 papers met our inclusion criteria from seven countries published 2007–2017. Findings were presented from a total of 644 participants and 153 programme providers. Participants described being attracted to programmes that were perceived to be novel or exciting, as well as being endorsed by their healthcare provider. The sense of belonging to a group who shared similar issues, and who had similar physiques and personalities, was particularly important and seemed to foster a strong group identity and related accountability. Group-based activities were enjoyed by many and participants preferred WMPs with more intensive support. However, some described struggling with physical activities (due to a range of physical comorbidities) and not everyone enjoyed group interaction with others (sometimes due to various mental health comorbidities). Although the mean BMI reported across the papers ranged from 36.8 to 44.7 kg/m2, no quotes from participants in any of the included papers were linked to specific detail regarding BMI status.Conclusions Although group-based interventions were favoured, people with severe obesity might be especially vulnerable to physical and mental comorbidities which could inhibit engagement with certain intervention components.